Teams in Small Organizations: Conceptual, Methodological, and Practical Considerations - Reiter-Palmon, Roni; Kennel, Victoria L.; Allen, Joseph A. (Frontiers in Psychology, 2021)
Research on teams and teamwork has flourished in the last few decades. Much of what we know about teams and teamwork comes from research using short-term student teams in the lab, teams in larger organizations, and, more recently, teams in rather unique and extreme environments. The context in which teams operate influences team composition, processes, and effectiveness. Small organizations are an understudied and often overlooked context that presents a rich opportunity to augment our understanding of teams and team dynamics. In this paper, we discuss how teams and multi-team systems in small organizations may differ from those found in larger organizations. Many of these differences present both methodological and practical challenges to studying team composition and processes in small complex organizational settings. We advocate for applying and accepting new and less widely used methodological approaches to advance our understanding of the science of teams and teamwork in such contexts.